Pengembangan Strategi Pembelajaran Pendidikan Agama Islam (PAI) dalam Merespon Era Digital - Tang, Muhammad (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2018)
In today's digital era, people generally think that the current learning of Islamic Religious Education (PAI) has been considered a failure to instill moral / religious values ​​to learners. This can be seen by the many crimes committed by teenagers who are students. For example; begal, drug abuse, brawl, promiscuity and other forms of crime. The failure of learning PAI, according to the author one of the reasons is because in general learning PAI done in monotonous and conventional. Therefore, as PAI educators / teachers should be innovative and creative in developing learning strategies that are interesting and fun for learners. So the values ​​of Islamic education can be well internalized in the learners. This paper comes to dissect and offer the concept of PAI learning strategies that are integrative in response to the development of technological tools in the digital era today. This paper uses the method of library research with a critical-analysis approach, thus giving birth to a concept or model of learning strategy that is integrative between religious values, science and technology.